Parallel implementations of TSP brute force algorithm - Almenara Ventura Alves, Rafael; Bentes, Cristiana; S. Castro, Maria Clicia (Cadernos do IME - Série Informática, 2024)
The traveling salesman problem is a famous combinatorial optimization problem. Despite its great importance, there is no good exact solution for the generic case. Considering the existence not only of CPUs with many cores but also of GPUs allowing a more generic use and being more popular, this work tries to answer the question: up to what size of problem is it possible to solve in parallel through brute force in a timely manner? For this, implementations were developed in OpenMP, MPI, and CUDA.